Multigrid Methods for Elliptic Partial Differential Equations - Rania Taleb Mohammad Wannan (My University, 2010)
Partial differential equations appear in mathematical models that describe natural phenomena. Various methods can be used for solving such equations. In this thesis, an overview of classical iterative methods, as well as, the most recent multigrain methods is given. The classical iterative methods used are; the Jacobi, the Gauss-Seidel, and the SOR methods. Jacobi and Gauss-Seidel methods are efficient in smoothing the error but not in reducing it. The smoothing property of some classical methods motivated the work done on multigrain methods. Poisson's problem in one and two dimensions has been used as model problem in the study of multigrain methods. The study shows that the rate of convergence of multigrain methods does not depend on the mesh size, a feature that makes multigrain methods good accelerator of classical methods like Gauss-Seidel.

المعادلات التفاضلية الجزئية تظهر في الأنظمة الرياضية التي تصف الظواهر الطبيعية. طرق مختلفة يمكن استعمالها لحل مثل هذه المعادلات. في هذه الاطروحة ستتم مراجعة عامة للطرق التقليدية وكذلك الطرق المتعددة الشبكات الأحدث . الطرق التقليدية المستخدمة هي طريقة جاكوبي وطريقة جاوس-سايدل و طريقة SOR . طريقة جاكوبي وطريقة جاوس-سايدل تعتبر جيدة في تنعيم الخطأ ولكن ليس في تصغيره، صفة التنعيم حفزت العمل على الطرق متعددة الشبكات. معادلة بواسون في البعدين الاول والثاني استخدمت كنموذج لهذه الدراسة. هذه الدراسة بينت ان سرعة التقارب لهذه الطرق لا تعتمد على البعد بين النقاط. هذه الخاصية جعلت الطرق متعددة الشبكات مسَرع جيد للطرق التقليدية.
طرق متعددة الشبكات للمعادلات التفاضلية الجزئية الناقصة